2021
DOI: 10.1007/s00213-021-06000-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PSD95/nNOS by ZL006 alleviates social isolation-induced heightened attack behavior in mice

Abstract: Rationale Deregulated attack behaviors have devastating social consequences; however, satisfactory clinical management for the behavior is still an unmet need so far. Social isolation (SI) has been common during the COVID-19 pandemic and may have detrimental effects on mental health, including eliciting heightened attack behavior. Objectives This study aims to explore whether injection of ZL006 can alleviate SI-induced escalation of attack behavior in mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…It is known that nNOS inhibition can cause aggressive behavior [ 54 ]. A recent study showed that the nNOS-PSD-95 pathway mediates the SI-induced escalation of attack behavior and the dissociation of nNOS-PSD-95 by ZL006 mitigates SI-induced escalated attack behaviors in mice [ 91 ], suggesting a promising therapeutic strategy for treating aggressive behaviors.…”
Section: Nnos-psd-95 Interaction and Neuropsychiatric Disordersmentioning
confidence: 99%
“…It is known that nNOS inhibition can cause aggressive behavior [ 54 ]. A recent study showed that the nNOS-PSD-95 pathway mediates the SI-induced escalation of attack behavior and the dissociation of nNOS-PSD-95 by ZL006 mitigates SI-induced escalated attack behaviors in mice [ 91 ], suggesting a promising therapeutic strategy for treating aggressive behaviors.…”
Section: Nnos-psd-95 Interaction and Neuropsychiatric Disordersmentioning
confidence: 99%
“…In adults, social isolation has been also reported to enhance aggression in several male rodent species such as wild and lab mice, rats, and hamsters (Borland et al 2019;Elliott Albers et al 2006;Koolhaas et al 2013;Miczek et al 2001Miczek et al , 2013Ross et al 2019;Yang et al 2022b;Zelikowsky et al 2018). In adult females, the effects of social isolation on aggressive behavior have been less studied (Oliveira and Bakker 2022).…”
Section: Social Isolation and Aggressive Behaviormentioning
confidence: 99%
“…Total 2 weeks of social isolation was found to stimulate NO synthesis in the cortex of male mice; this was followed by high levels of aggression. Furthermore, inhibition of NO synthesis using ZL006, an NMDA-R-dependent NO synthesis inhibitor targeting specifically neuronal nitric oxide synthase (nNOS)/PSD95, reduced aggressive behavior in isolated mice (Yang et al 2022b). Conversely, isolated nNOS-KO mice were found to display a higher number of attacks, boxing, and decreased attack latency compared to isolated wild types.…”
Section: Adulthood Neurobiological Mechanismsmentioning
confidence: 99%
“…In adults, social isolation has been also reported to enhance aggression in several male rodent species such as wild and lab mice, rats, and hamsters (Borland et al 2019;Elliott Albers et al 2006;Koolhaas et al 2013;Miczek et al 2001Miczek et al , 2013Ross et al 2019;Yang et al 2022b;Zelikowsky et al 2018). In adult females, the effects of social isolation on aggressive behavior have been less studied (Oliveira and Bakker 2022).…”
Section: Social Isolation and Aggressive Behaviormentioning
confidence: 99%